Meninjau Penerapan Community-Based Tourism di Desa Wisata Karangrejo, Borobudur: Stakeholder Mapping Analysis - Aulia, Finda Elfa; Subakti, Isroq Adi; Khoirini, Iwanda Luthfi; Anggraeni, Larissa Dewi; Trisnawati, Nadilla; Putri, Pratiwi Ayu (JURNAL NASIONAL PARIWISATA, 2024)
Karangrejo Tourism Village, Borobudur District, Magelang Regency, Central Java Province applies the concept of Community Based Tourism (CBT) in tourism management by involving various stakeholders in it. However, in its management, not all stakeholders have the same power and interest, as well as the roles they have. Through this study, the mapping of stakeholders and their roles in tourism management in Karangrejo Tourism Village will be further described. This study uses a qualitative method to map stakeholders who play a role in the development and management of Karangrejo Tourism Village using primary and secondary data through interviews, observations, and literature studies. The results of the study show that the implementation of CBT in Karangrejo Tourism Village has a positive impact on the economic, social, cultural, environmental, and political dimensions. Also the differences in power and interest and roles between stakeholders, including local communities, government apparatus (village and regional), the private sector, and international organizations. The conclusion of the study highlights the success of the implementation of CBT and the importance of mapping the stakeholders involved to avoid overlapping roles and increase collaboration between them.